2017
DOI: 10.1016/j.stem.2017.11.002
|View full text |Cite
|
Sign up to set email alerts
|

Dye-Independent Methods Reveal Elevated Mitochondrial Mass in Hematopoietic Stem Cells

Abstract: Hematopoietic stem cells (HSCs) produce most cellular energy through glycolysis rather than through mitochondrial respiration. Consistent with this notion, mitochondrial mass has been reported to be low in HSCs. However, we found that staining with mitotracker green, a commonly used dye to measure mitochondrial content, leads to artifactually low fluorescence specifically in HSCs because of dye efflux. Using mtDNA quantification, enumeration of mitochondrial nucleoids and fluorescence intensity of a geneticall… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

15
122
1
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 175 publications
(139 citation statements)
references
References 33 publications
15
122
1
1
Order By: Relevance
“…In line with this, de Almeida et al . demonstrated that HSCs have higher mitochondrial mass and lower mitochondrial turnover than mature haematopoietic cells, a contradiction to previously established literature . These results suggest that the elevated levels of autophagy reported in HSCs compared to their more differentiated counterparts are not indicative of mitophagy upregulation.…”
Section: Interplay Between Autophagy and Oxidative Stress In Lscscontrasting
confidence: 88%
“…In line with this, de Almeida et al . demonstrated that HSCs have higher mitochondrial mass and lower mitochondrial turnover than mature haematopoietic cells, a contradiction to previously established literature . These results suggest that the elevated levels of autophagy reported in HSCs compared to their more differentiated counterparts are not indicative of mitophagy upregulation.…”
Section: Interplay Between Autophagy and Oxidative Stress In Lscscontrasting
confidence: 88%
“…Our theory therefore suggests that inhibition of basal mitophagy may be able to slow down the rate of random genetic drift, and perhaps healthy aging, by locking-in low levels of heteroplasmy. Indeed, it has been shown that mouse oocytes (Boudoures et al, 2017) as well as mouse hematopoietic stem cells (de Almeida et al, 2017) have comparatively low levels of mitophagy, which is consistent with the idea that these pluripotent cells attempt to minimise genetic drift by slowing down mtDNA turnover. A previous modelling study has also shown that mutation frequency increases with mitochondrial turnover (Poovathingal et al, 2009).…”
Section: Targeting Mitophagy Rate Against Mutant Expansionssupporting
confidence: 61%
“…[156][157][158][159][160][161][162] Yet recent studies demonstrated instead that hematopoietic stem cells have substantial mitochondrial mass as visualized by electron microscopy and show robust labeling with Mitotracker dyes when pretreated with verapamil, an inhibitor of ABC drug transporters. 163 As another example of how drug manipulations should be treated with caution, we performed pharmacological experiments with plasma cell subsets and etomoxir, an inhibitor of fatty acid oxidation, to define the carbon sources that drive basal respiration. Our results suggested that approximately 50% of basal respiration is derived from long-chain fatty acids.…”
Section: Methods To Assess Plasma Cell Metabolismmentioning
confidence: 99%